Body weight perception and body weight control behaviors in adolescents - Robson Frank; Gaia S. Claumann; Érico P.G. Felden; Diego A.S. Silva; Andreia Pelegrini (Brazilian Society of Pediatrics, 2018)
Objective: To investigate the association between the perception of body weight (as above or below the desired) and behaviors for body weight control in adolescents. Methods: This was a cross‐sectional study that included 1051 adolescents (aged 15-19 years) who were high school students attending public schools. The authors collected information on the perception of body weight (dependent variable), weight control behaviors (initiative to change the weight, physical exercise, eating less or cutting calories, fasting for 24 h, taking medications, vomiting, or taking laxatives), and measured body weight and height to calculate the body mass index and then classify the weight status. Associations were tested by multinomial logistic regression analysis. Results: Adolescents of both sexes who perceived their body weight as below the expected weight took more initiatives to gain weight, and those who perceived themselves as overweight made more efforts to lose weight. In adolescents who perceived themselves as overweight, the behavior of not taking medication was associated with the outcome only in boys (OR = 8.12), whereas in girls, an association was observed with the variables eating less, cutting calories, or avoiding fatty foods aiming to lose or avoid increasing body weight (OR = 3.39). Adolescents of both sexes who practiced exercises were more likely to perceive themselves as overweight (male OR = 2.00; OR = 1.93 female). Conclusion: The perception of the body weight as above and below one's expected weight was associated with weight control behaviors, which were more likely to result in initiatives to lose and gain weight, respectively.